1996
DOI: 10.1111/j.1472-765x.1996.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of conjugative plasmid pAMβ1 from Lactococcus lactis to mouse intestinal bacteria

Abstract: Conjugal transfer of plasmid pAM beta 1 from Lactococcus lactis to intestinal bacteria of BALB/c mice was studied. Plasmid transfer was observed to Enterococcus faecalis in vitro by a filter mating method with transfer frequencies of 2.3 x 10-3 and with lower frequencies to other species. In vivo, using gastric intubation with the pAM beta 1-bearing Lactococcus lactis as donor and Ent. faecalis as recipient, a few transconjugants were detected from faecal Ent. faecalis. However, when these mice were given eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…There is evidence that gene transfer can occur within the intestinal tract of mice (51). The ycdB gene has an unknown function and is widespread in bacteria (some enteric bacteria have two copies) and some eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that gene transfer can occur within the intestinal tract of mice (51). The ycdB gene has an unknown function and is widespread in bacteria (some enteric bacteria have two copies) and some eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…Only a limited number of studies have investigated in vivo antibiotic resistance transfer of pAM␤1 plasmid from L. lactis donors to the human gastrointestinal microbiota (54) or to mouse intestinal bacteria (27). In vivo transfer of the Tn916 transposon was observed previously in the intestinal tract, but from E. faecalis donor strains (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the diassociated model pAMβ1 has been transferred from L. reuteri to Enterococcus faecalis (Morelli et al, 1988). Interspecies conjugative transfer of tetracycline and erythromycin resistance plasmids from lactobacilli has been demonstrated previously in vitro (Gevers et al, 2003a;Ouoba et al, 2008;Feld et al, 2008 Transfer has been demonstrated in the GIT of rodents, both gnotobiotic (Feld et al, 2008;Jacobsen et al, 2007;Morelli et al, 1988) and those having an indigenous gut microbiota (Feld et al, 2008;Jacobsen et al, 2007;Schlundt et al, 1994;McConnell et al, 1991;Gruzza et al, 1994;Igimi et al, 1996). In addition, the in vivo transfer of vancomycin resistance has recently been shown between enterococci and probiotic lactobacilli in gnotobiotic mice (Mater et al, 2008).…”
Section: Evidence Of Potential Horizontal Gene Transfer Of Probiotic mentioning
confidence: 99%